A corrupção e o ambiente contábil dos países - Botinha, Reiner Alves (2018)
In order to elucidate the role of accounting in a scenario of corruption, this study aimed to explore how the quality of the accounting environment of countries is associated with the degree of perceived corruption. The sample of the survey lists 66 countries and a sum of 287,196 observations of companies between the periods of 2008 and 2015. It was verified that the accounting, political, economic and cultural environments exert influence in reducing the perceived degree of corruption. The variables considered by the literature as determinants for the reduction of perceived corruption, which did not provide consensus in previous studies, were the adoption of IFRS and the opacity of the results. In the present study, neither the adoption of IFRS nor the opacity of the results were statistically significant in the models tested. Alternatively, as a representative variable of the accounting environment, the perceived quality of accounting was pointed out as being one of the determinants in reducing corruption perceived in the present study. Increased disclosure and greater frequency of Big Four audits do not appear to be associated with perceived corruption. Therefore, the search for providing quality accounting information and reducing the levels of informational asymmetry are factors that may help to mitigate the corruption scenario. It is expected that the research contributes to the literature by proposing a better characterization of the accounting environment to mitigate the corruption scenario. For the accounting practice, it is expected to have indicated possible benefits of a better disclosure of the accounting information to strengthen the accounting environment and increase the sense of responsibility of the professionals. The thesis that the levels of perceived corruption of countries are influenced by their accounting environment, controlled economic, political and institutional and cultural factors was confirmed in this study.